Breast meat characteristics of broilers fed fermented mixture of cassava pulp and Moringa oleifera leaf meal - Sugiharto, S.; Widiastuti, E.; Isroli, I.; Yudiarti, T.; Sartono, T. A.; Wahyuni, H. I. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
The present study aimed to investigate the effect of feeding fermented mixture of cassava pulp and M. oleifera leaf meal (FCPMO) on the breast meat characteristics of broiler chickens. From day 8 onward, 400 Lohmann broiler chicks were allotted to four dietary groups included CONT (maize-soybean-based feed with no additive), BACI (maize-soybean-based feed supplemented with 0.1% zinc bacitracin), FERM (feed containing 20% of FCPMO) and FERB (feed containing 20% of FCPMO and 0.1% probiotic Bacillus subtilis). At day 35, one male chick from each replicate (10 chicks per treatment group) was taken and slaughtered. After being eviscerated and de-feathered, sample of breast meat was obtained for the assessment of meat characteristics. Results showed that feeding FCPMO had no effect (P>0.05) on pH and water holding capacity (WHC) of breast meats. Compared to other groups, FERB meat had higher (P<0.05) cooking loss. FERM and FERB meats had lower (P<0.05) moisture content than that of CONT and BACI meats. Feeding FCPMO with or without B. subtilis increased (P<0.05) crude protein content of breast meats. Feeding FCPMO resulted in lower (P<0.05) fat content in the breast meat. Compared to other meats, breast meats from BACI had higher (P<0.05) ash content. Cholesterol was lower (P=0.08) in FERB than in BACI and FERM meats. The 2,2-diphenylpicrylhydrazyl (DPPH) IC50 values were higher (P<0.05) in meat of CONT than that in other groups. Feeding FCPMO resulted in higher (P<0.05) polyunsaturated fatty acids (PUFA), lower (P<0.05) monounsaturated fatty acids (MUFA) and had no effect on saturated fatty acids (SFA) contents of broiler breast meats. In conclusion, feeding FCPMO produced healthy broiler meat as reflected by the higher contents of protein, PUFA and antioxidants, and lower fat in meats.